Heat shock alleviation effect of Angelica gigas nakai root hot water extract through immunomodulation and enhancement of heat shock protein expression in murine splenocytes - Lumbera, Wenchie Maria L. (Animo Repository, 2015)
Heat stress represses different components of the immune system thereby making animals prone to diseases. Many studies demonstrated the immunostimulatory potential of Angelica gigas Nakai (AGN) but its potential in ameliorating heat stress in accordance with immunomodulation have not been discovered. In this study, we investigated the immunomodulatory mechanism of AGN root hot water extract in alleviating the deteriorating effects of heat shock specifically to the immune function using murine splenocytes. Murine splenocytes was subjected to heat shock procedure by incubating at 42 ̊C for one hour then allowed to recover for one hour at 37 ̊C prior to mitogen stimulation, treatment of AGN and incubated for both 12 and 24 hours. Cell viability assay was done to compare the effect of AGN on the proliferation of normal and heat shocked murine splenocytes. Results showed alleviation of heat shock with the dose dependent (0-400μg/ml) increase in cell proliferation of normal and heat shocked splenocytes for both 12 and 24 hours. RT-PCR was undertaken to evaluate the expression of heat shock gene, proteins (HSF1, Hsp90, Hsp70, Hsp60 and Hsp27) and cytokines (IL-1β, IL-2, IL-6, TNFα and IFNγ) in protecting and activating splenocytes, respectively. Western blot analysis of heat shock gene and proteins was done to further demonstrate the ameliorating effect in the level of protein expression. AGN dose dependently increased both mRNA and protein expression of HSF1, Hsp90, Hsp70, Hsp60 and Hsp27 indicating its potential for heat stress remedy. The upregulated expression in RT- PCR of IL-1β and IL-6 implied a Th2 immunomodulatory response. The increase in TNFα and IFNγ expression signify pro-inflammatory, anti-viral and anti-tumor potential of AGN extract. These findings provided the potential of AGN in ameliorating unwanted effects of heat stress through enhanced heat shock protein expression and Th2 immune response modulation.